Penyuluhan Integrasi Pendidikan Karakter dalam Membentuk Anak Tangguh di Era Digital di Desa Cikedokan Bekasi - Azi Matur Rahmi; Gina Asri Ruwaida (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Community service (PKM) activities are implemented to help improve teachers' and parents' understanding of character education. The rise in bullying among students negatively impacts every aspect of their behavior and mental well-being. To improve the quality of early childhood education, counseling is essential in every learning process. Therefore, community service activities are required by every lecturer to fulfill the Tri Dharma of Higher Education (Tri Dharma) requirements. This community service program is designed to provide intensive training in strengthening character education for children. This training is expected to equip them with practical skills and a deeper understanding of the integration of character education by fostering collaboration between parents and the community, thereby shaping student character in accordance with the vision of a Golden Indonesia. These include the integration of character values into learning, character-based digital literacy skills, mental and emotional resilience, positive social behavior in the real and digital worlds, and educational environmental support.